Impact of established cardiovascular disease on outcomes in the randomized global leaders trial. Issue 7 (19th December 2019) - Garg, Scot; Chichareon, Ply; Kogame, Norihiro; Takahashi, Kuniaki; Modolo, Rodrigo; Chang, Chun‐Chin; Tomaniak, Mariusz; Fath‐Ordoubadi, Farzin; Anderson, Richard; Oldroyd, Keith G.; Stables, Rod H.; Kukreja, Neville; et al.
Abstract: Objective: To investigate the impact of different anti‐platelet strategies on outcomes after percutaneous coronary intervention (PCI) in patients with established cardiovascular disease (CVD). Methods: GLOBAL LEADERS was a randomized, superiority, all‐comers trial comparing one‐month dual anti‐platelet therapy (DAPT) with ticagrelor and aspirin followed by 23‐month ticagrelor monotherapy (experimental treatment) with standard 12‐month DAPT followed by 12‐month aspirin monotherapy (reference treatment) in patients treated with a biolimus A9‐eluting stent. Established CVD was defined as ≥1 prior myocardial infarction, PCI, coronary artery bypass operation, stroke, or established peripheral vascular disease. The primary endpoint was a composite of all‐cause death or new Q‐wave MI at 2‐years. The secondary safety endpoint was BARC 3 or 5 bleeding. Exploratory secondary endpoints were the patient‐orientated composite endpoint and net adverse clinical events. Results: Among the 15, 761 patients in this cohort were 6, 693 patients (42.5%) with established CVD. Compared to those without established CVD, these patients had significantly higher rates of the primary (5.1 vs. 3.3%, HR1.59[1.36–1.86], p < .001) and secondary composite endpoints with no significant differences in bleeding. There was a nonsignificant reduction in the primary endpoint in patients with established CVD receiving the experimental treatment (4.6 vs. 5.6%, HR0.82[0.66–1.02], p = .07). When comparing patients without CVD to those with one or three territories of CVD, the hazard ratio for the primary endpoint increased in unadjusted and adjusted models. Conclusions: The poorer outcomes in patients with established CVD are not mitigated by prolonged monotherapy with a potent P2Y12 inhibitor suggesting a greater need to focus on modifiable risk factors.